Peningkatan Kapasitas Pokdarwis dalam Pengelolaan Wisata Berkelanjutan Air Terjun Tayak di Desa Uren Kabupaten Balangan - Fatullah, M; Zulaikha, Siti; As'ad, M. Farhan; Norkamaliah; Hairiah; Inawati, Dike; Camelia, Aulia Syifa; Nabiella, Zahwa Fatika; Sabila, Nur; Zahara, Nabila Az; Alfina, Nor Azizah; Nugraha, Adimahsa (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
Tayak Waterfall is located in Uren Village, Halong District, Balangan Regency, with the pristine natural beauty of the Meratus Mountains. Its geographical location in the Meratus Mountains gives this waterfall the potential to become a sustainable nature-based tourist destination. In the context of tourism development, the role of Pokdarwis is very important as the main driver of the management of the Tayak Waterfall tourist destination. The community service program carried out by the service team aims to improve the management and promotion of Tayak Waterfall tourism through strengthening the Pokdarwis organizational structure, digital promotion, and administrative improvements. Activities carried out include social media management workshops, logo creation, social media account development, barcode and entrance ticket innovation, and registration of a Business Identification Number (NIB) as legal proof of tourism business. These workshops not only focused on improving technical skills but also on strengthening Pokdarwis members' awareness of the importance of sustainable tourism management. Pokdarwis members were given an understanding of digital communication strategies, creative and interesting content management, and the importance of destination branding in increasing tourist appeal. Despite facing obstacles such as low participation of Pokdarwis members and limited internet access, the program succeeded in improving the knowledge and skills of Pokdarwis members, strengthening the organizational structure, and enhancing the digital promotion of tourist destinations. The results are expected to increase tourist appeal, the sustainability of Tayak Waterfall tourism management, economic benefits for the local community, and the preservation of the surrounding environment. Through the implementation of workshops and ongoing mentoring activities, this program has strengthened Pokdarwis' capacity to design sustainable tourism development strategies that are adaptive to technological developments. The program emphasizes the importance of community collaboration and the use of digital technology as key drivers in sustainable tourism development.